The Intergrowth of Gold Precipitation base on Drift Effect in Pongkor Gold Mine - Nur Ali Amri; Abdul Aziz Jemain; Wan Fuad wan Hassan; Jatmika Setiawan (Jurnal Ilmu Kebumian Teknologi Mineral (JIK TekMin), 2015)
ABSTRACTOne of semi-variogram modeling utilities in geology used to determine the control of mineralization. The paper discusses the existence of gold mineralization. The grade samples of gold (Au) were transformed into logarithmic function as base of variogram estimation. Parameter of fitting based on spherical weighted least squares. Eight directions used for estimation with angle tolerance of 11.25o. Several parameters obtained from calculation based on robust experimental function, four of them selected as reliable value. The drift effect occurs in Northeast-Southwest start at the lag distance of 325.05m, which has 32 samples of pair points. This drift direction is perpendicular from vein where Au distributed and indicated of Au mineralization.Keyword: Variogram, anisotropic geometry, drift effect, mineralization. ABSTRACTSalah satu kegunaan pemodelan variogram di dalam geologi adalah mengetahui kontrol mineralisasi. Tulisan ini mendiskusikan keberadaan mineralisasi. Sampel grade dari Au ditransformasi ke fungsi logaritma, sebagai basis estimasi variogram. Parameter fitting merujuk pada model weighted least squares fungsi sferis. Delapan arah digunakan dalam mengestimasi, dengan memanfaatkan toleransi jarak 11.25o. Atas dasar perhitungan fungsi eksperimental robust diperoleh beberapa parameter utama, empat di antaranya dipilih sebagai nilai yang reliabel. Informasi diperoleh bahwa efek drift terjadi pada arah Utara-Selatan yang dimulai pada jarak lag 325.05 m, di mana terdapat 32 pasangan sampel titik. Arah drift ini tegak lurus vein dimana Au terdistribusi dan mengindikasikan arah aliran mineralisasi Au.Keyword: Variogram, anisotropic geometry, drift effect, mineralization.